Development of autonomous all-terrain vehicle (A2TV) steering and bracking module - Sheikh Muhammad Alif Asyraf, Sheikh Mohd Mazlan (2021)
This thesis deals with enhancement of the steering system and the autonomous ATV braking system. Steering is one of the important part that have in the All-terrain Vehicle that was use to control the movement left and right. The second part that are important is the brake part. The brake are important to support the system when the ATV a moving in different position. The function of brake are to stop the ATV from moving or to stop the ATV from hit the Obstacle at front of the ATV. ATV are important in few sector in the world. One of the sector that are important is the agriculture sector. Many worker are facing back pain in this sector. The reason is the sector are using heavy farm tool that will damage the health of the worker. Furthermore, the process of poisoning the plant one of the most danger task. The worker will expose to the toxic gas that can effect the worker health. The development of Autonomous ATV is to help the worker to reduce back pain or slip disk. The autonomous ATV can help worker to bring heavy to and also can help worker form prevent the toxic gas that cause from poisoning the plant. The system that can control the autonomous to bring heavy tool and for poisoning the plant without human are involve in the area. The system will remove the manual mechanical part from the ATV and will replace with autonomous system for better product and performance of the product.